Herd behaviour in financial markets: an experimental approach - Nguyen, Thien Kim (2020)
This thesis uses the experimental approach to examine the existence, the characteristics and the consequences of herd behaviour in financial markets. We conduct three experiments, which are asset market (Smith, Suchanek and Williams, 1988), information cascade (Anderson and Holt, 1997) and Holt and Laury (2002). We found that herd behaviour due to information asymmetry and reputation presences in all experimental financial markets. Participants decided to follow the market since they believe other participants have more information, or other participants performed better than themselves. Interestingly, herd behaviour is not a threat for price bubbles, volatility and market efficiency. Individual characteristics and personalities are found to be significantly correlated with herding decisions. The thesis includes four essays, in which each essay presents the results from one of the three experiments. The last essay analyses the impacts of the big five personality traits on investment decisions. The results from this thesis are beneficial for investors, academics and policy-makers.